Fertility duration in indigenous hens following controlled mating, and growth performance of their offspring - Muhumuza, Ivan; Kasoro, Isaac; Asiimwe, Brian; Kugonza, Donald Rugira (Taylor & Francis Group, 2026)
In Uganda, indigenous chickens constitute 70% of the poultry population, but their reproductive efficiency is affected by insufficient fertility data. This study evaluated the fertility duration in indigenous hens after mating and compared the growth performance of their offspring with that of Broiler and Kuroiler chickens. Thirty-six indigenous hens from three districts were assigned to four pens of eight hens each. Twelve cocks were introduced in batches for a 2-week mating period following a 3-week hen isolation phase. Eggs were collected weekly over 15 weeks, incubated, and candled on day 13 to assess fertility. Chicks hatched from these eggs were monitored for growth and compared with Broiler and Kuroiler chicks for 14 weeks. The average egg fertility post-mating was 75%, with fertile eggs laid approximately 87.3 h after mating, while fertility declined to 49.6%, 3 weeks post-cock removal, with effective fertility lasting approximately 7.12 days. Live body weight was highest in broilers and lowest in indigenous chickens at all ages until the broilers left the study at five weeks. Among indigenous and Kuroiler chickens, cocks were significantly heavier (P < 0.05) than hens at all ages. To enhance fertility and optimize egg production in smallholder systems, weekly mating of indigenous hens is recommended.
Keywords: Indigenous hens; fertility duration; offspring; growth; breeding